Role of the Variant Rs3774261 of Adiponectin Gene on Cardiovascular Risk Factors and Adiponectin Levels After a High Fat Hypocaloric Diet with Mediterranean Pattern - Luis, Daniel de; Primo, David; Izaola, Olatz; Bachiller, Rosario (Cardiology and Cardiovascular Medicine, 2021)
Background: The role of ADIPOQ gene on serum lipid and adiponectin levels after a dietary intervention remained unclear. Some polymorphisms have been described in this gene that they could interact with metabolic changes after diet intervention. Objective: Our aim was to analyze the effects of a high fat hypocaloric diet with a Mediterranean dietary pattern on metabolic response and adiponectin levels taking to account of rs3774261 of ADIPOQ. Design: A population of 284 obese patients was enrolled. Anthropometric parameter and serum parameters (lipid profile, insulin, homeostasis model assessment (HOMA-IR), glucose, C reactive protein, adiponectin, resistin and leptin levels) were measured, at basal time and after high fat hypocaloric diet (12 weeks). All patients were genotyped in the rs3774261. Results: The genotype distribution was; 78 patients (27.5%) AA, 144 patients AG (50.7%) and 62 patients GG (21.8%). After a significant weight loss secondary to diet intervention (AA vs. AG vs. GG); total cholesterol (delta:-15.1 ± 2.9 mg/dl vs. -7.2 ± 2.1 mg/dl vs. -5.0 ± 1.9 mg/dl; p=0.03), LDL cholesterol (delta:-14.1 ± 2.9 mg/dl vs. -6.4 ± 1.8 mg/dl vs. -3.2 ± 2.0 mg/dl; p=0.01), triglyceride levels (delta:-26.0 ± 4.6 mg/dl vs 6.4 ± 3.3 mg/dl vs. -5.7 ± 2.9 mg/dl; p=0.01), C reactive protein (CRP) (delta:-2.4 ± 0.1 mg/dl vs -1.3 ± 0.2 mg/dl vs. -0.7 ± 0.1 mg/dl; p=0.01) and serum adiponectin levels (delta: 17.6 ± 3.9 ng/dl vs. 1.9 ± 3.3 ng/dl vs. 2.1 ± 1.3 ng/dl; p=0.02) improved only in AA group. Conclusion: Subjects with AA genotype of ADIPOQ variant (rs3774261) showed a significant increase in serum levels of adiponectin and decrease on lipid profile and C-reactive protein (CRP) after weight